Business tax burden in the non-linear system - Zholayeva, M.A.; Chaya, V.T. (BUKETOV BUSINESS REVIEW, 2019)
Tax burden affect economic performance by changing incentives for business formation in the non-linear system, expansion and operation. In the article the definition of tax burden as an integrated feature of the impact of taxation on the business entity. Authors specify the sources of spending between the tax rate and tax revenues, there is a nonlinear relationship. Raise the notion of tax schemes. On the basis of the studied materials the allocation of tax revenues between levels of budget was considered. Author’s opinion is justified from the standpoint of complex nonlinear doctrine; the main functions of the tax burden at the micro level were defined. Authors describe in details the order of their finding, note the time lag for which it is advisable to determine the tax burden of an entity in the nonlinearity. The tax burden of the enterprise in a nonlinear system should not be. The State can and should regulate the rational development of small and medium-sized businesses in the tax load of the enterprise in a complex nonlinear system. Efficient design of a business tax system encourages activities with beneficial economic spillovers and imposes lighter burdens on those industries and activities that are most responsive to taxation. Tax reforms have the potential to improve economic efficiency by adjusting the level and design business burden in the non-linear system.